Distinct and targetable role of calcium-sensing receptor in leukaemia - Pereira, Raquel; Kumar, Rahul; Cais, Alessia; Paulini, Lara; Kahler, Alisa; Bravo, Jimena; Minciacchi, Valentina R.; Krack, Theresa; Kowarz, Eric; Zanetti, Costanza; Godavarthy, Parimala Sonika; Hoeller, Fabian; et al. (Nature Communications, 2023)
Haematopoietic stem cells (HSC) reside in the bone marrow microenvironment (BMM), where they respond to extracellular calcium [eCa2+] via the G-protein coupled calcium-sensing receptor (CaSR). Here we show that a calcium gradient exists in this BMM, and that [eCa2+] and response to [eCa2+] differ between leukaemias. CaSR influences the location of MLL-AF9+ acute myeloid leukaemia (AML) cells within this niche and differentially impacts MLL-AF9+ AML versus BCR-ABL1+ leukaemias. Deficiency of CaSR reduces AML leukaemic stem cells (LSC) 6.5-fold. CaSR interacts with filamin A, a crosslinker of actin filaments, affects stemness-associated factors and modulates pERK, β-catenin and c-MYC signaling and intracellular levels of [Ca2+] in MLL-AF9+ AML cells. Combination treatment of cytarabine plus CaSR-inhibition in various models may be superior to cytarabine alone. Our studies suggest CaSR to be a differential and targetable factor in leukaemia progression influencing self-renewal of AML LSC via [eCa2+] cues from the BMM.
Gesehen am 01.08.2024